MEMPREDIKSI KEADAAN SUMUR DIMASA DEPAN DENGAN MELAKUKAN OPTIMASI MENGGUNAKAN ELECTRICAL SUBMERSIBLE PUMP PADA SUMUR “AD-96” - Muhammad Adnan; Rohima Sera Afifah; Yudiaryono Yudiaryono (PETROGAS: Journal of Energy and Technology, 2021)
The production capacity of an oil and gas well is a benchmark in planning production equipment and increases the flow rate of production. In order to increase the rate of oil production, optimization is done optimally using ESP and it is predicted that the production time will be several years ahead. The method used in the well "AD-96" is the Wiggins Method 3 Phase IPR curve to increase the optimal production flow rate by continuing to predict IPR Future through a gradual decrease in reservoir pressure (Pr) scenario. IPR Future in this case provides a development to know the wells in the future. The results of the calculation of Wiggins IPR curve on the well "AD-96" obtained a maximum production rate (Qmax) of 2469 bfpd. To estimate the optimal production rate obtained from a percentage of 80% x maximum flow rate of 1975 bpd, the well is advised to use the Electrical Submersible Pump design with the ESP REDA type pump type DN1800 Pump Performance Curve 60 Hz, 3500 rpm and a Horse Power of 29 HP. , efficiency 76% and IPR Future with water cut of 80% each carried out in the calculation of 4 scenarios at 2000 psia reservoir pressure, obtained a target production flow rate (Qtarget) of 1326 bpd. It is known that the recommended production (recommended production) is between 1200-2400 bpd. Based on the IPR Future scenario, the result shows that ESP does not work at a pressure of 2000 psia.